Penerapan Metode Content-Based Filtering Pada Sistem Rekomendasi Kegiatan Ekstrakulikuler (Studi Kasus di Sekolah ABC) - Firmahsyah Firmahsyah; Tiur Gantini (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Abstract— ABC School is an educational organization. They operate their routine activities without information systems, especially for extracurricular activies. System recommendation was made to help the school. It provides to recommend extracurricular which is more suitable with student interest. Primary data source is obtained by interview and observation with headmaster of ABC School. Primary data used for analysis and design sytem. The analysis use one of data mining technique, which is content based recommendation. The content based recommendation method that used for this research is Naïve Bayes. The result of this research is a recommendation system to show propability the extracurricular fo each student with some chosen attributes.   Keywords—  attribute, information gain, Naïve Bayes,   recommendation system